Comparing tractive performance of steel and rubber single grouser shoe under different soil moisture contents - Jun, Ge; Xiulun, Wang; Kito, Koji (International Journal of Agricultural and Biological Engineering, 2016)
Steel and rubber are two kinds of materials which are often used for the tracks of off-road vehicles. The objective of this study was to compare tractive performances of steel and rubber grouser shoes under different soil moisture contents. In this study, the tractive performance of single grouser shoe was predicted by soil parameters and three-dimensional shearing model. The soil used in this study was clay soil, and ten different soil moisture contents ranged from 8.58% to 54.36% were applied for investigation of soil parameters. For each soil moisture content, the penetration test, direct shearing test, density and soil moisture content measurement have been performed to obtain the required soil parameters. The experimental results showed that thrust and running resistance of steel single grouser shoe had similar trends to those of rubber single grouser shoe. The thrust of rubber single grouser shoe was always greater than that of steel single grouser shoe with the increase of soil moisture content, and as well as the running resistance. However, the traction of rubber single grouser shoe had a different trend to that of steel single grouser shoe. The traction of steel single grouser shoe was always greater than that of rubber single grouser shoe at any given moisture content except at the stage of less than 15% moisture content. From the experimental results, it can be concluded that the steel single grouser shoe performed better than rubber single grouser shoe in traction for the soil used in this study.Keywords: steel grouser shoe, rubber grouser shoe, soil moisture content, tractive performance, running resistance, tracked vehicleDOI: 10.3965/j.ijabe.20160902.1688Citation: Ge J, Wang X L, Kito K. Comparing tractive performance of steel and rubber single grouser shoe under different soil moisture contents. Int J Agric & Biol Eng, 2016; 9(2): 11－20.